(untitled) (Global Journal of Human-Social Science, 2014)
Advertisement frequently employs children object as model to promote certain product/service. Children explo-itation in advertisement is of course will affect the model or the audience, so that it gets positive or negative respond from the consumer. The appearance of advertisement employing children model sometimes breaks the ethical code or advertisement etiquette. This breach cannot be repressed by certain parties, thus it affects directly the children’s mental growth and development.